THE INFLUENCE OF JOB SATISFACTION ON SPECIALIST PHYSICIANS’ PERFORMANCE MEDIATED BY PUNCTUALITY IN OUTPATIENT SERVICES(AN EMPIRICAL STUDY AT DR. SAIFUL ANWAR REGIONAL GENERAL HOSPITAL, EAST JAVA PROVINCE) - Budianto, Mochamad Bachtiar; Rudijanto, Achmad; Wardhani, Viera (Journal of Community Health and Preventive Medicine, 2025)
Job satisfaction plays a vital role in enhancing productivity, particularly in hospitals that function as integral components of the healthcare system and provide various services, with outpatient care often serving as the primary access point to referral hospitals. Optimal human resources and service quality can only be attained when employees experience job satisfaction, which in turn promotes greater productivity, creativity, discipline, enthusiasm, and commitment. High job satisfaction encourages a positive attitude toward work, whereas dissatisfaction tends to lead to a negative impact on performance. This study aims to examine the effect of job satisfaction on the performance of specialist physicians, with punctuality as a mediating variable in the outpatient department of Dr. Saiful Anwar Regional General Hospital, East Java Province. This research employed an analytical observational design with data collected cross-sectionally. The study population comprised 100 specialist physicians working in the outpatient installation, selected using purposive sampling. Data were gathered through questionnaires and electronic attendance records, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that punctuality mediates the relationship between job satisfaction and performance (t = 3.812; p = 0.001 < 0.05). Strategies such as remuneration improvements, reward and punishment systems, standard operating procedures (SOPs), and enhancement of facilities and infrastructure are expected to improve both satisfaction and performance among specialist physicians in outpatient services.